Urejanje zemljišč - pomembno področje geodezije - Prosen, Anton (Geodetski vestnik, 1998)
The article gives an analysis of a new domain within geodesy, land development and land management. In addition to the interpretation and comments on several terms used, we also attempted to define new tasks arising within this new domain
Keywords: geodezija; upravljanje; urejanje; zemljišča